2015
DOI: 10.1021/acs.jced.5b00405
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Vapor–Liquid Equilibrium for the Ternary Mixture HFC-32 + HFC-125 + HFC-161 at Temperatures from 265.15 K to 303.15 K

Abstract: The ternary mixture HFC-32 + HFC-125 + HFC-161 was considered as a potential alternative refrigerant to HCFC-22 and HFC-410A for the environmentally friendly and excellent thermodynamic properties. Vapor−liquid equilibrium data are necessary for the mixed refrigerant to evaluate its optimal composition and the cycle performance in the refrigeration cycles. On the basis of this, the vapor−liquid equilibrium data for the mixture HFC-32 + HFC-125 + HFC-161 were investigated by the experiment. The vapor−liquid equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…where the V T is volume of the cell and the unit of it is cm 3 . The mass of empty cell (m 2 ) and the mass of the cell containing the sample (m 1 ) were measured by the precision analytical balance with a resolution of 0.5 mg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where the V T is volume of the cell and the unit of it is cm 3 . The mass of empty cell (m 2 ) and the mass of the cell containing the sample (m 1 ) were measured by the precision analytical balance with a resolution of 0.5 mg.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, much research on alternative fluids was published. Mixed refrigerants including binary mixtures, ternary mixtures, and even quaternary mixtures were proposed to meet the requirements of thermal efficiency, safety, and low toxicity. , It was reported that some of the mixed refrigerants had favorable characteristics with respect to the environment . Sheng et al reported the pρTx and specific heat capacity of the (R290+R1243zf) mixture .…”
Section: Introductionmentioning
confidence: 99%
“…For use in residential and lowcapacity commercial air conditioning and heat pumps, the EPA lists R452B, R454B, R454C as acceptable alternatives in addition to R32 [22]. Apart from these refrigerants, R290 [25,32], R161 [33], R152a [34], R466A [35] and R1234yf [25,34] are also specified as alternatives for R410A and R404. The properties of the refrigerants mentioned in Tab.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, many brilliant investigations have been reported on the performance of ejector refrigeration systems and most of them were tested with hydrofluorocarbons (HFC) refrigerants, such as HFC-134a, HFC-245fa, HFC-236fa, HFC-141b and HFC-152a. However, due to their high GWPs [12] , they will be surely substituted by more environment-friendly refrigerants in the coming future [13] . Recently, some new fourth-generation refrigerants are proposed, such as hydrofluoroolefin (HFO)/ hydrochlorofluoroolefin (HCFO) refrigerants.…”
Section: Introductionmentioning
confidence: 99%